Agronomic efficiency of ‘Cantaloupe’ melon under different water blades and organic fertilization - Irineu, Toni Halan da Silva; Figueredo, Lucimara Ferreira de; Figueredo, Janailson Pereira de; Silva, Josimar Nogueora da; Paiva, Jacinto Rômulo Guedes de; Andrade, Raimundo (Comunicata Scientiae, 2018)
The objective of this study was to evaluate the effect of different irrigation blades on the presence and absence of biofertilizer on the agronomic performance of the ‘Cantaloupe’ melon in the Paraíba backwoods. The work was conducted under field conditions in the Agroecology Sector, belonging to the State University of Paraíba (UEPB), Campus IV. The experimental design was a randomized block using four irrigation blades (60, 80, 100 and 120% - ET0, (mm day-1)) with presence and absence of biofertilizer replicated six times. The following variables were evaluated: main branch length, leaf area, number of leaves, phytomass aerial part, pulp diameter, soluble solids, bark diameter, number of seeds per fruit, seed weight per fruit and weight of 100 seeds. The irrigation blade of 120% of ET0 promoted greater growth and development since biofertilizer application provided a greater number of seeds per fruit and weight of 100 seeds, there was no interaction between the factors studied in both variables evaluated in the Cantaloupe melon.